Guide to using the National Electrical Code (NEC) - Greg Fletcher (Thomson Delmar Learning, 2007)
Written in accordance with the 2005 National Electrical CodeÂđ, this new book is designed to provide straightforward, easy-to-understand explanations of how to use and apply the CodeÂđ. Readers with little or no electrical experience can learn how to use the NECÂđ to find must-know information quickly. The Guide to Using the National Electrical CodeÂđ contains the essential information for determining the minimum requirements for installing electrical wiring and equipment in a safe and proper manner. Coverage has been thoughtfully arranged to clearly explain the basic information and the use of the NECÂđ, which is vital to understanding how to meet Code requirements for safe electrical installations